Health belief model in pregnant women in the free nutritional meal program: a review - Rosdiana; Utami, Nendhi Wahyunia; Sunarsih, Tri; Astuti, Endah Puji; Shanti, Elvika Fit Ari (MEDIA ILMU KESEHATAN, 2025)
Background: Stunting is still a serious problem in Indonesia, one of which is caused by malnutrition since pregnancy.Objective: To systematically identify and map the use of HBM in understanding pregnant women's compliance with nutritional intervention programs, especially free nutritious meals.Methods: This scoping review was conducted based on the Arksey and O'Malley framework and followed the PRISMA-ScR guidelines. The literature was searched through the PubMed, ScienceDirect, and Google Scholar databases in 2018–2025. The studies reviewed were original studies with a quantitative, qualitative, or mixed methods approach that used HBM in pregnant women.Results: From 12 selected studies, it was found that HBM components such as perceived benefits, barriers, and cues to action had a significant effect on the nutritional behavior of pregnant women. Driving factors include culture-based education, family support, and the use of educational media. Meanwhile, the main barriers include economic constraints, food access, and cultural norms.Conclusion: HBM effectively understands pregnant women's behavior in the free nutritious meal program. HBM-based educational interventions integrated with community approaches and digital technology are recommended to improve the program's effectiveness.